2020
DOI: 10.1186/s12955-020-01413-0
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life among 13–14 year old adolescents with overweight−a mixed methods approach

Abstract: Background: Overweight and obesity are public concerns with risk of adverse health outcomes. Health-related quality of life (HRQoL) is lower in adolescents than children in general. An increase in body mass index (BMI) is associated with a decrease in HRQoL. The purpose of this study was to measure and explore the HRQoL among adolescents with overweight or obesity who had participated in an intervention study, Young & Active, with the aim of increasing physical activity (PA), reducing BMI and promoting HRQoL. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
(71 reference statements)
2
5
0
Order By: Relevance
“…The starting point of this cross-sectional study conducted on a sample of early adolescent students was that Italian girl adolescents, considering the single variables of HRQoL, had lower scores in psychological dimensions, in line with previous evidence obtained in a European sample, in which boys reported higher physical appearance, self-esteem, and mood dimensions [11,12,[18][19][20][21][22]. When we considered HRQoL as a function of the different BMI categories, we observed that in females, this relationship was much closer than that found in males.…”
Section: Discussionsupporting
confidence: 85%
“…The starting point of this cross-sectional study conducted on a sample of early adolescent students was that Italian girl adolescents, considering the single variables of HRQoL, had lower scores in psychological dimensions, in line with previous evidence obtained in a European sample, in which boys reported higher physical appearance, self-esteem, and mood dimensions [11,12,[18][19][20][21][22]. When we considered HRQoL as a function of the different BMI categories, we observed that in females, this relationship was much closer than that found in males.…”
Section: Discussionsupporting
confidence: 85%
“…This finding confirms previous research. 21 , 22 Future studies are required to clarify gender discrepancies in HRQoL and explore the relationship between gender and HRQoL in Nigerian adolescents in the postpandemic era.…”
Section: Discussionmentioning
confidence: 99%
“…Such factors include personal demographic factors such as age, gender, and body mass index (BMI). 21 , 22 However, limited or no evidence exists on the relationship among PA domains, levels, HRQoL, and BMI among adolescents in sub-Saharan Africa, including Nigeria. 23 25 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical, mental, social, psychological and behavioural aspects of well-being were distinguished as components. Emphasis was placed on the multidimensional nature of the quality of life, as well as the subjective evaluation of one's own well-being [1,6,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%